Disease detection in the eye with machine learning techniques - Vibin Mathiparambil Vinod (Nanyang Technological University, 2024)
With AI becoming more prevalent in the healthcare industry, this project explores the integration of machine learning and deep learning techniques in the field of ophthalmology. There is a need for accurate and efficient diagnosis as the traditional approaches often require lengthy consultations and screenings.